Analisis Tingkat Motivasi Belajar Siswa Dalam Pembelajaran Daring Pada Mata Pelajaran Matematika - Nanda Ayu Sasami; Krisdianto Hadiprasetyo; Erika Laras Astutiningtyas (Universitas Veteran Bangun Nusantara, 2021)
The purpose of this study was to find out how the level of sudent motivation in online learning in mathematics in class XI MIPA SMA Negeri 1 Weru in the academic year 2019/2020 and to find out how students’ motivation to learn in each indicator. This research uses descriptive method with a qualitative approach. Data collection techniques used in this study in the form of a questionnaire. The result showed that the level of student motivation in online learning in mathematics in the class XI MIPA of SMA Negeri 1 Weru in academic year 2019/2020 was included in the medium category. With the percentage of students’ motivation in each indicator that is in indicator 1 (Perseverance in doing the assignment) of 66,53% so that it is included in the sufficient category, in indicator 2 (Resilient in facing difficulties) by 69,19% so that it is included in the sufficient category, at indicator 3 (Happy working independently) by 68,01% so that it is included in the sufficient category, in indicator 4 (There is encouragement and needs in learning) by 67,47% so it is included in the sufficient category, indicator 5 (Showing interest) 0f 55, 38% so it is included in the category of not good, in indicator 6 (Can maintain confidence) of 69,35% so that it is included in the sufficient category, in indicator 7 (Happy to find and solve answers to mathematical problems) of 64,11% so that it is included in enough categories.